2022
DOI: 10.1172/jci147191
|View full text |Cite
|
Sign up to set email alerts
|

KLF2 regulates neutrophil activation and thrombosis in cardiac hypertrophy and heart failure progression

Abstract: It is widely recognized that inflammation plays a critical role in cardiac hypertrophy and heart failure. However, clinical trials targeting cytokines have shown equivocal effects indicating the need for a deeper understanding of the precise role of inflammation and inflammatory cells in heart failure.Leukocytes from human subjects and a rodent model of heart failure were characterized by a marked reduction in expression of KLF2 mRNA. Using a mouse model of Angiotensin II-induced non-ischemic cardiac dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 74 publications
(91 reference statements)
0
45
1
Order By: Relevance
“…There are, for example, no specific and effective treatments for heart failure with preserved ejection fraction, a condition commonly characterized by left ventricular hypertrophy ( 2 , 4 ). In this issue of the JCI , Tang et al provide a translationally provocative contribution to the understanding of nonischemic cardiac hypertrophy and failure ( 6 ).…”
Section: Neutrophils In Cardiac Hypertrophymentioning
confidence: 99%
See 4 more Smart Citations
“…There are, for example, no specific and effective treatments for heart failure with preserved ejection fraction, a condition commonly characterized by left ventricular hypertrophy ( 2 , 4 ). In this issue of the JCI , Tang et al provide a translationally provocative contribution to the understanding of nonischemic cardiac hypertrophy and failure ( 6 ).…”
Section: Neutrophils In Cardiac Hypertrophymentioning
confidence: 99%
“…One recent study showed that neutrophil depletion reduces cardiac hypertrophy and dysfunction induced by pressure overload (i.e., transverse aortic constriction) in mice ( 7 ). Tang et al provide evidence that neutrophils contribute to cardiac hypertrophy and dysfunction induced by angiotensin II ( 6 ).…”
Section: Neutrophils In Cardiac Hypertrophymentioning
confidence: 99%
See 3 more Smart Citations